Rational reprogramming of the sesquiterpene synthase BcBOT2 yields new terpenes with presilphiperfolane skeleton. Issue 1 (30th November 2022) - Nikolaiczyk, Vanessa; Irwan, Jenny; Nguyen, Trang; Fohrer, Jörg; Elbers, Philipp; Schrank, Paul; Davari, Mehdi D.; Kirschning, Andreas
Abstract : Computer-aided rational design allowed to create variants of the sesquiterpene cyclase BcBOT2 that yielded novel tricyclic presilphiperfolane-type sesquiterpenes. Abstract : Computer-aided rational design of the substrate binding pocket of sesquiterpene synthases BcBOT2 from Botrytis cinerea yielded FPP cyclization products with presilphiperfolane backbone other than the naturally formed sesquiterpene presilphiperfolan-8β-ol. Particularly, amino acids W118 and F138 were found to strongly control the stability and conformation of key cationic intermediates. The W118Q variant forms only presilphiperfolan-9β-ol, whereas the exchange of amino acids at position 138, such as F138V, has a fundamental effect on the course of the cationic cascade. Here, the 1, 3-hydride shift en route to presilphiperfolan-8β-ol is suppressed and substituted by a so far unknown 1, 2-hydride shift that leads to presilphiperfol-1-ene and presilphiperfolan-1α-ol along with β-caryophyllene and the so far unknown caryophyllene-8β-ol.